Hazing in South African schools and school hostels: a media analysis - Wet, Corene de (Acta criminologica, 2017)
Despite the banning of hazing in 2002, it is still a fairly common practice in some South African schools and school hostels. This paper uses newspaper articles as a data source and draws on the theories of cognitive dissonance and dominance to study hazing. A qualitative content analysis of 41 newspaper articles provides insight into the nature of hazing; the education context in which hazing occurs; the views of parents, educators and learners on this illegal practice; as well as the reasons for the perpetuation thereof. The study concludes that hazing practices are effected through the advocacy of its so-called character and team-building qualities and the vilification of those who speak out against this ‘time-honoured tradition’. Adolescents’ need for acceptance and their fear of being scorned, result in their rationalising the practice and its consequent acceptance. It is recommended that schools develop and adopt anti-hazing policies.